THE INFLUENCE OF CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, FIRM SIZE ON FIRM VALUE: FINANCIAL PERFORMANCE AS MEDIATION VARIABLE - Laili, Choirun Nisful; Djazuli, Atim; Indrawati, Nur Khusniyah (Jurnal Aplikasi Manajemen, 2019)
This study aims to examine and analyze the effect of directly or indirectly between the variables of corporate governance, corporate social responsibility, firm size, the financial performance of the company with the sample value amounted to 53 companies engaged in the manufacturing sector with years of observations from 2015 to 2017. Methods of data analysis using path analysis with AMOS software 24. Corporate governance is proxied by the Corporate Governance Index (CGI), corporate social responsibility is proxied by the Corporate Social Responsibility Index (CSRI), firm size is proxied by Size, financial performance proxied by Return on Assets (ROA), and the value of the company is proxied by Tobin’s Q. The results showed that the direct effect of the test results show that 1) corporate social responsibility, firm size effect on financial performance. 2) Corporate social responsibility, firm size, financial performance affects the value of the company 3) corporate governance does not affect the company’s financial performance and value. As for the indirect effect of the test showed that corporate governance, corporate social responsibility, firm size, to the value of the company through the financial performance of no significant impact. Therefore, the three did not mediate financial performance affects the value of the company 3) corporate governance does not affect the company’s financial performance and value. As for the indirect effect of the test showed that corporate governance, corporate social responsibility, firm size, to the value of the company through the financial performance of no significant impact. Therefore, the three did not mediate financial performance affects the value of the company 3) corporate governance does not affect the company’s financial performance and value. As for the indirect effect of the test showed that corporate governance, corporate social responsibility, firm size, to the value of the company through the financial performance of no significant impact. Therefore, the three did not mediate.